1977
DOI: 10.1002/aja.1001500305
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopy of the connective tissues between longitudinal and circular muscle of small intestine of cat

Abstract: Electrotonic spread of applied potentials was observed between longitudinal and circular muscle layers of the small intestine with no rectification. Nexal junctions were demonstrated between muscle fibers of each layer. Connective tissue cells bridged between the two muscle layers. These showed structural characteristics of fibrocytes and of interstitial cells. Some nexuses were seen between connective tissue cells and between these cells and muscle fibers of each layer but in most junctions the membranes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

1977
1977
1999
1999

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…The arrow indicates one ICC. Sentithin section, toluidine blue, x 800. belong to the connective-tissue family, as suggested by Taylor et al [1977], Gabella [1979] and Komuro [1982].…”
Section: Discussionmentioning
confidence: 99%
“…The arrow indicates one ICC. Sentithin section, toluidine blue, x 800. belong to the connective-tissue family, as suggested by Taylor et al [1977], Gabella [1979] and Komuro [1982].…”
Section: Discussionmentioning
confidence: 99%
“…There must be relatively low-resistance current paths between the two muscle layers. Electron microscopic observations reveal an abundance of interstitial cells and fibrocytes in the region between the muscle layers which make junctional contacts with muscle fibres of each layer and with each other (Taylor, Kreulen & Prosser, 1977). Since fibroblasts can serve as passive conductors between clusters of embryonic heart fibres, (Hyde, Blondel, Matter, Cheneval, Filloux & Girandier, 1969), it is probable that interstitial cells and fibrocytes provide low-resistance paths between the intestinal muscle layers.…”
Section: Discussionmentioning
confidence: 99%
“…In the cat, slow waves recorded in longitudinal muscle and in cells between the two muscle layers were not different, suggesting strong electrical coupling. Indeed, anatomical studies have shown the presence of fibroblasts (Taylor, Kreulen & Prosser, 1977), interstitial cells (Thuneberg, 1982) and smooth muscle cells (Kobayashi et al 1967) connecting the two muscle layers; this structural interconnexion may provide a functional interaction. Such interconnexions have not been observed in the canine gastrointestinal tract (Daniel & Sarna, 1978).…”
Section: Discussionmentioning
confidence: 99%